Corporate Strategies to Improve Platform Economic Performance: The Role of Technology, Ethics, and Investment Management - Abigail Leffia; Sheila Aulia Anjani; Marviola Hardini; Sondang Visiana Sihotang; Qurotul Aini (Pandawan Sejahtera Indonesia, 2024)
Amid the rapid growth of the platform economy, companies are feeling the pressure to adopt innovative technologies to improve their performance. Meanwhile, in an effort to achieve sustainable growth, ethical issues also arise that must be resolved. This research aims to investigate how the integration of technology and ethical principles can contribute to improving corporate performance in the platform economy environment. We explore how companies can overcome the dilemmas that arise when they adopt advanced technologies while also considering deep ethical aspects. This research methodology involves the SmartPLS approach to analyze the relationship between technological variables and ethical variables on company performance, involving 120 participants. It is hoped that the results of this research will provide valuable insight into how companies can optimize the use of technology while still adhering to strong ethical principles, with the aim of achieving superior performance in the competitive platform economy market. Thus, this research provides a significant contribution in understanding how companies can achieve sustainable excellence amidst changing economic dynamics.